Investigation of microstructure and corrosion propagation behaviour of nitrided martensitic stainless steel plates - Abidin, K.A.Z. (EDP Sciences, 2014)
Martensitic stainless steels are commonly used for fabricating components. For many applications, an increase in surface hardness and wear resistance can be beneficial to improve performance and extend service life. However, the improvement in hardness of martensitic steels is usually accompanied by a reduction in corrosion strength. The objective of this study is to investigate the effects of nitriding on AISI 420 martensitic stainless steel, in terms of microstructure and corrosion propagation behavior. The results indicate that the microstructure and phase composition as well as corrosion resistance were influenced by nitriding temperatures. Â© 2014 Owned by the authors, published by EDP Sciences.